Diseño e implementación de guías y módulos didácticos para el laboratorio de automatización industrial en la carrera de ingeniería eléctrica campus Kennedy - Lemus Bedoya, Anabel Alexandra (2012)
The preset work previous to obtain the Electrical Engineer degree, was developed for that Polytechnic Salesian University campus Kennedy in Quito has new guides for Industrial Automation II Labs, the new guides were design according the actual requirements for professional life and academics concepts. The new guides will find to provide the best technology for teaching and use the latest equipment acquired by the Polytechnic Salesian University. The new guides for labs practices were creating for that students improve their skills and obtain the best professional features for their future life, the new guides help the students to learn cooperative work, to think in the needs of world, are self-training and encourage investigation. Each guide has theorical information, examples, challenges to development, encourage investigation, bibliographic information, bill of materials and spaces for comments and recommendations. The new guides for labs practices were design for the students can use all elements and material that Polytechnic Salesian University had bought and implemented in each lab.